EFFECTIVENESS OF PARTITION WATER BITTER MELON AGAINST DECREASE IN BLOOD SUGAR EXPERIMENTAL DIABETIC MALE RATS - Yudha, Dwi Widananta Yogi Indra; Suartha, Nyoman; Sudimantini, Luh Made (Buletin Veteriner Udayana; Vol. 10 No. 1 Pebruari 2018DO - 10.24843/bulvet.2018.v10.i01.p02, 2018)
The aims of this research are to find out the effectiveness of water partition Momordicia charantia fruit to the decrease blood glucose of experimental diabetic male rats ( Rattus norvegicus ). This research used twenty 3 months old male rats which were adapted for 2 weeks. Rat grouped into 4 groups namely the negative control (P0), only given food and drink alone; positive controls (P1), was given only feed, drink, and streptozotocin; EP group (P2), was given food, drink, streptozotocin, and extra bitter melon 2%; water partition group was given feed, drinking water and partitions streptozotocin 50 mg / kg body weight. Streptozotocin giving conducted on days 0, giving extract bitter melon and water partition conducted from day 3 to day 20. Measurement of glucose conducted on days -1, 0, 4, 11 and 18. The obtained data were evaluated using one-way ANOVA test. The results showed that water partition Momordicia charantia fruit could decrease blood glucose levels in a dose of 50 mg / kg of body weight significantly compared with the positive control.